Aqueous Benzylic C−H Trifluoromethylation for Late-Stage Functionalization - Guo, Shuo (J Am Chem Soc, 2018)
The installation of trifluoromethyl groups has become an essential step across a number of industries such as agrochemicals, drug discovery, and materials. Consequently, the rapid introduction of this critical functional group in a predictable fashion would benefit current practitioners in those fields. This communication describes a mild trifluoromethylation of benzylic C−H bonds with high selectivity for the least hindered hydrogen atom. The reaction provides monotrifluoromethylation and proceeds in an environmentally friendly acetone/water solvent system. The method can be used to install benzylic trifluoromethyl groups on highly functionalized drug molecules.